Optimizing Long-Lasting Insecticidal Nets Campaign in Ivory Coast - Irineu de Brito; Silvia Uneddu; Emma Maspero; Paulo Gonçalves (Logistics)
This research supports the United Nations Children’s Fund’s (UNICEF) conceptualization, planning and implementation of a campaign for distribution of more than 12 million mosquito nets in Ivory Coast. Procured from four different suppliers in Asia, the nets were transported to the two ports in Ivory Coast before being pre-positioned at 71 Health Districts across the country, a mixed integer network flow model identifies optimal transport options. The process of modeling and the model developed in this paper brought a significant understanding of the problem and, consequently, a reduction in the overall procurement and logistics costs. The implications of using mathematical modeling by practitioners as a tool which contributes to solve humanitarian logistics problems are significant. Mathematical models, like linear programming, can greatly support overall decision-making within humanitarian organizations by helping to ensure that limited resources are used in the most cost-effective and efficient manner. However, it is important to ensure consultations with and involvement by on the ground practitioners to ensure developed solutions assessed to fit the operating context before being implemented.